P1775CMV VIREMIA IN KIDNEY TRANSPLANT RECIPIENTS RECEIVING BASILIXIMAB OR LOW DOSE ANTI THYMOCYTE GLOBULIN INDUCTION WITHOUT VALGANCICLOVIR PROPHYLAXIS- SINGLE CENTRE EXPERIENCE IN INDIA. (6th June 2020) - Sharma, Reetesh; Maksana, Mayur; Trehan, Naresh
Abstract: Background and Aims: CMV is a major cause of morbidity in transplant recipients and manifests as tissue invasive disease or CMV viral syndrome. Controversy exists regarding best method for CMV prevention. Therefore, we intended to evaluate incidence of CMV viremia and symptomatic CMV infection in adult KTR with basiliximab or antithymocyte globulin (ATG) induction without the use of valganciclovir prophylaxis. This study will help developing a protocol for management of CMV infection/disease in Indian patients since there is no such data amongst Indians. Method: A prospective, open-label, single centre study. Patients were monitored for CMV DNA-PCR twice a week for month 1 post-transplant, once a week in month2, and then every 2 weeks in month 3, and then once a month from month 4 to 6. Results: We included 17 patients with low-dose ATG induction (group1) and 20 patients with Basiliximab induction (group2). Mean recipient age was 42.9 and 45.9 yr in group 1 and 2 whereas mean donor age was 50.6 and 51.6 yr respectively. Male recipients were 76.4% (13/17) and 65% (13/20) in group 1 and 2 respectively; male donors were 11.7% (2/17) and 20% (4/20) respectively (not signficant). Average HLA mismatches were 3.4/6 and 3.7/6 (not significant). In group1 average transfusions per patient were 6units (vs 1.7units in group2) and 65% pts in group1 had >3 units transfusion (p<0.05). Mean follow-up was 12.7 and 20.7 months respectively. Incidence of acute rejection was 5.8% (1/17) and 10% (2/20) in group 1 and 2 respectively. (not significant). Incidence of CMV viremia requiring valganciclovir therapy was 11.6% (2/17) and 10% (2/20) in group 1 and 2 respectively. (not significant). No patient developed CMV disease. Mean serum creatinine was 1.1 and 1.09 mg/dL at 1 month and 1.2 and 1.14 mg/dL at 3 months (not significant) Conclusion: The incidence of CMV viremia is low and not significantly different in patients receiving basiliximab or low dose ATG induction in living donor kidney transplants on tacrolimus based immunosuppression. In our study patients in ATG group had significantly more transfusions vs basiliximab group and hence were more sensitised. Still the incidence of acute rejection remained low in both these groups (5.8% and 10%). Hence universal prophylaxis with valganciclovir may not be required in all the patients with basiliximab and low dose ATG induction especially in developing countries where cost of therapy is borne by the patients.